Critical Analysis of Decentralization Theory in the Context of Local Government: A Literature Review - Fifi Febriandiela; Aldri Frinaldi; Lince Magriasti (Adabi : Journal of Public Administration and Business, 2024)
This article examines multiple elements that impact the outcome of decentralization in the context of local governance. The success of decentralization is heavily contingent upon the robustness of regional institutions, the political dynamics at play, and the unique attributes of the country undertaking the reform, as indicated by a comprehensive analysis of existing literature. Efficient decentralization necessitates well-defined institutional procedures, political solid and civil determination, enhancement of capabilities, and democratic governance. Nevertheless, notable obstacles include the possibility of heightened corruption, involvement from local politics, and discrepancies between the legal framework and real-world implementation. Hence, meticulous planning, contextual adaptations, and vigilant supervision are vital to guarantee accountability and effectiveness in executing decentralization. A literature review conducted with consistent and suitable methodological approaches is a form of qualitative research, specifically within the realm of literature study. This is employed inductively to prevent the emergence of more inquiries. The rationale behind undertaking qualitative research lies in its inherent exploratory nature. A comprehensive analysis is conducted in the part dedicated to the relevant literature or literature review. The research findings indicate that decentralization is an intricate and thorough approach whose effectiveness heavily relies on each nation's social, political, and economic circumstances. Robust and responsible local institutions guarantee high-quality public services and mitigate corruption. Decentralization strategies necessitate customization to suit the unique circumstances of each country since a uniform strategy will not be effective universally. The local political dynamics heavily influence the success of decentralization. The effects of decentralization can be influenced by cultural identities and ideological differences, which can affect community trust and involvement and potentially lead to exclusion and instability. Implementing decentralization frequently encounters substantial obstacles, such as the possibility of heightened corruption and political instability.